(untitled) (National Administration Journal, 2025)
We navigate a digital environment saturated with content of various kinds, which requires marketing strategies to connect with the audience and prioritize their experience. In this scenario, storytelling is an important strategic tool to differentiate a brand, build an emotional connection with audiences, and strengthen effective brand management.This article discusses the production process of two enrollment campaigns from the Universidad Estatal a Distancia (UNED) of Costa Rica, based on stories of students and graduates whose narratives go beyond simply conveying information to generate engagement, build trust, and guide purchase decision-making during quarterly enrollment.Using a qualitative action-research methodology, an open call is made to both populations during the 2024–2025 period, and stories are developed for radio, press, television, and social media, demonstrating that well-crafted narratives trigger empathy and memory, overcoming resistance to traditional advertising.